2011
DOI: 10.1021/ef200249a
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of Water-in-Oil Emulsions in Radio-Frequency and Microwave Electromagnetic Fields

Abstract: This paper investigates the problem of destroying highly stable water-in-oil emulsions. The high stability of water-inoil emulsions is primarily caused by the presence of heavy, high-molecular-weight polar components in oil that envelope water droplets and that prevent these droplets from combining (coalescing). Using conventional techniques in this case yields no positive results. Employing electromagnetic energy is one way to address this problem. This paper presents the results of experimental studies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 18 publications
0
11
0
2
Order By: Relevance
“…The microwave treatment was said to be enhanced by the addition of salts because they increased the dielectric properties of the aqueous phase. Comparisons between microwave and conventional heating have been attempted [8,11,15,16] but are limited by the difficulty in measuring absorbed power, temperature and temperature distribution during microwave heating. These difficulties have led to the proposal that non-thermal microwave effects exist, which subsequently lead to a reduction in zeta-potential [4,5,12,16], and that "the magnetic field formed by the microwave makes the non-polar oil molecules magnetise and form a spiral electric field that subtends an angle with the axis of the oil molecule" [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The microwave treatment was said to be enhanced by the addition of salts because they increased the dielectric properties of the aqueous phase. Comparisons between microwave and conventional heating have been attempted [8,11,15,16] but are limited by the difficulty in measuring absorbed power, temperature and temperature distribution during microwave heating. These difficulties have led to the proposal that non-thermal microwave effects exist, which subsequently lead to a reduction in zeta-potential [4,5,12,16], and that "the magnetic field formed by the microwave makes the non-polar oil molecules magnetise and form a spiral electric field that subtends an angle with the axis of the oil molecule" [7].…”
mentioning
confidence: 99%
“…Comparisons between microwave and conventional heating have been attempted [8,11,15,16] but are limited by the difficulty in measuring absorbed power, temperature and temperature distribution during microwave heating. These difficulties have led to the proposal that non-thermal microwave effects exist, which subsequently lead to a reduction in zeta-potential [4,5,12,16], and that "the magnetic field formed by the microwave makes the non-polar oil molecules magnetise and form a spiral electric field that subtends an angle with the axis of the oil molecule" [7].However, the rationale or physical basis for these effects is not fully explained and the exact mechanisms of microwave assisted demulsification are still not fully understood.The aim of the work reported in this paper is to investigate these mechanisms with the hypothesis that the phenomena observed during microwave assisted emulsification can be explained by selective and volumetric heating and heat and mass transfer Page 6 of 25 processes. This knowledge will enable comparison of microwave assisted demulsification with demulsification by conventional heating methods, which will be required to assess the commercial potential of this process.…”
mentioning
confidence: 99%
“…In the case of microwave heating, the model suggested that the distribution of the thermal field inside the water droplet was spatially uneven, and the authors suggested that this may cause local ruptures of the armour envelope surrounding the droplet, leading to a multitude of small droplets being formed from the single large droplet. These studies [2,[8][9][10][11] demonstrate the ability of microwave treatment to enhance demulsification. However, they used commercially available microwave systems that operate at constant temperature, and therefore the incident (and absorbed) power varied between runs, making assessment of the effect of different parameters difficult.…”
Section: Improving the Separation Of Water-in-oil Emulsions -Enhancinmentioning
confidence: 99%
“…There are various ways of transfering heat energy from the source to the medium and inductive and electromagnetic heating are among these. In recent years, the use of high-frequency changing EM fields has become a widely used technology for heating complex hydrocarbon systems (Carrizales et al, 2008;Kasevich et al, 1994;Kovaleva et al, 2008Kovaleva et al, , 2011aKovaleva et al, , 2011bBientinesi et al, 2013). The urgency of this technology is connected with the fact that, for the considered media, it is important not only to reduce the viscosity by heating, but to a greater extent to destroy stable structures of high-molecular hydrocarbon compounds by the effect of electromagnetic radiation.…”
Section: Introductionmentioning
confidence: 99%